Assessing the physical activity of daily living among the elderly at retirement homes / Wan Noor Anira Wan Ali @ Yaacob, Nur Huzeima Mohd Hussain and Nadiyanti Mat Nayan - Wan Ali @ Yaacob, Wan Noor Anira; Mohd Hussain, Nur Huzeima; Mat Nayan, Nadiyanti (2021)
Regular physical activities (PA) at the green outdoor lead to improved health for the elderly, enabling them to be healthy for a prolonged period. Activities Daily Living (ADLs) scale was developed by Sidney Katz in 1960 to measure the elderly ability to function, such as walking, bathing, and transferring (indoor and outdoor). Physical activity (PA) through Activities of Daily Living (ADLs) is an imperative and valuable way of enlightening coordination, maintaining independence, flexibility, balance, and muscle strength. The study aims to assess the significance of Activities of Daily Living (ADLs) methods to the needs of physical activity (PA) for the elderly in the green area. Activity of Daily Living (ADLs) is the potential mechanism to improve physical activity (PA) and supports social connection for the elderly. Assessing the elderly with Activity of Daily Living (ADLs) provides a useful starting point for describing the importance of green space for the elderly in long-term care facilities.